Thermal and aerodynamic characteristics of tube furnaces with wall burners of two types - Vafin D. B. (E3S Web of Conferences, 2019)
Tube furnaces of the petrochemical and oil refining industries are energy-intensive devices. The differential method for calculating the complex heat transfer in the furnaces is used to study the flow fields and the temperature of the combustion products in the radiation chambers of technological tube furnaces with two types of wall burners, which are placed on several levels on the sidewall. In a furnace designed for the conversion of methane mixed with steam in the reaction tubes, acoustic burners for burning natural gas near the wall are installed in three tiers on the side lined sidewalls of the radiation chamber. In the primary reforming furnace of natural gas for the production of ammonium nitrate, wall-type burners are installed on six levels. The method used is based on the joint numerical integration of the two-dimensional differential equations of energy transfer by radiation using the S2-approximation of the discrete ordinate method, the energy conservation equations, the equations of turbulent motion of a gas mixture, the k-e turbulence model and the two-stage gas fuel combustion model. The calculated fields of temperature and flue gas flow obtained with the help of a computer program implementing the proposed method are discussed.